Proceedings papers or journal articles: A tension in the scientific communication? - Miguel, Sandra (Anuario ThinkEPI, 2012)
Proceedings papers and journal articles play an important role in scholarly communication in most disciplines, including Library and Information Science. Although both serve different and complementary functions in scientific communication, in some cases the choice of one or the other can be exclusive and becomes a dilemma for researchers. This study aims to present different situations of tension caused by the choice of one or another channel of communication, and also an invitation to consider the role played by these two channels in the dissemination of scientific knowledge.
Keywords: Proceedings papers; Journal articles; Scholarly communication; Dilemma; Knowledge dissemination.